A stabilized tunable dual wavelength erbium-doped fiber laser with equal output power - Al-Alimi, A.W.; Al-Mansoori, M.H.; Abas, A.F.; Mahdi, M.A.; Adikan, Faisal Rafiq Mahamd; Ajiya, M. (IOP Publishing, 2009)
Tunable dual-wavelength erbium-doped fiber laser with good stability is experimentally demonstrated. Output power of as high as +5.26 dBm is obtained in dual ring configuration. Both laser output can be tuned to as closed as 0.8 nm spacing between each other, with tuning range of 31.33 nm. The stability of both outputs was tested that results in less than +/- 0.8 dB and +/- 0.01 nm in power and wavelength fluctuation, respectively.